DEVELOPMENT OF A SCIENTIFIC LITERACY INSTRUMENT BASED ON RIAU MALAY ETHNOSCIENCE IN SCIENCE SUBJECTS - Delfa Vioni Amalia; Aldeva Ilhami; Sa’diyatul Fuadiyah; Afdhal Kusumanegara (PEDAGOGIK : JURNAL PENDIDIKAN, 2024)
The OECD announced that the science literacy scores of Indonesian students ranked 70th out of 78 participating countries, indicating that science literacy in Indonesia is in the low category. One effort that can be made to improve students' science literacy is by incorporating local wisdom into learning assessments. The aim of this research is to determine the validity, practicality, and effectiveness of a science literacy instrument based on Riau Malay ethnoscience. This study uses the R&D research method designed using the Plomp model. The application of the Plomp model involves three stages: the preliminary research phase, the prototyping phase, and the assessment phase. The research instruments used include questionnaires, observation sheets, interview sheets, and science literacy test instruments based on Riau Malay ethnoscience. The data analysis techniques consist of qualitative and quantitative descriptive data analysis. Based on the data analysis results, the validity level of the test items is 88.16%, which falls into the valid category. The practicality level is 92%, which falls into the practical category. In the effectiveness stage, a score of 47.21% was obtained, which falls into the moderate category. The conclusion of this research is that the science literacy instrument based on Riau Malay ethnoscience is considered valid, practical, and suitable for use in science education.